2011
DOI: 10.3945/jn.110.135210
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Expression Protects Male Mice from High Fat–Induced Nonalcoholic Fatty Liver1–3

Abstract: Emerging evidence suggests that the lack of PPARα enhances hepatic steatosis and inflammation in Ppara-null mice when fed a high-fat diet (HFD). Thus, the aim of this study was to determine whether Ppara-null mice are more susceptible to nonalcoholic steatohepatitis (NASH) than their wild-type (WT) counterparts following short-term feeding with a HFD. Age-matched male WT and Ppara-null mice were randomly assigned to consume ad libitum a standard Lieber-DeCarli liquid diet (STD) (35% energy from fat) or a HFD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
210
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(230 citation statements)
references
References 41 publications
19
210
1
Order By: Relevance
“…In the current study, knockdown of Ppara also resulted in increased inflammation, necrosis, matrix remodeling, and evidence of stellate cell activation and fibrosis after feeding 70% HF diets relative to Wt mice. These data are consistent with previous studies on development of NASH in adult Ppara À/À mice fed high-fat diets 7 and similar to our previously published data on progression of alcoholic liver pathology in these mice. 8 Interestingly, and consistent with previous studies of NASH progression in the rat, 26 Cd44 mRNA, which encodes the major cell surface hyaluronan (HA) receptor, was significantly up-regulated in 70% HF diet-fed Ppara À/À mice.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the current study, knockdown of Ppara also resulted in increased inflammation, necrosis, matrix remodeling, and evidence of stellate cell activation and fibrosis after feeding 70% HF diets relative to Wt mice. These data are consistent with previous studies on development of NASH in adult Ppara À/À mice fed high-fat diets 7 and similar to our previously published data on progression of alcoholic liver pathology in these mice. 8 Interestingly, and consistent with previous studies of NASH progression in the rat, 26 Cd44 mRNA, which encodes the major cell surface hyaluronan (HA) receptor, was significantly up-regulated in 70% HF diet-fed Ppara À/À mice.…”
Section: Discussionsupporting
confidence: 83%
“…Deletion of Ppara has previously been shown to result in progression of liver pathology beyond simple steatosis to inflammation and fibrosis in adult mouse models of alcoholic and nonalcoholic liver disease. 6,7,22 The current data suggest a similar pattern of pathology when high polyunsaturated fat diets are fed to Ppara À/À mice beginning during early development. Increased evidence of oxidative stress, as indicated by increased oxidized glutathione/ reduced glutathione ratio and 4-Hne protein adducts, was observed in Ppara À/À compared to Wt mice fed 70% HF diets.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, it can limit interleukin (IL)-1-associated C-reactive protein expression [50,52] . In this regard, it has been shown that PPARα deficient mice are susceptible to hepatic steatosis and NASH [53][54][55] . The current concept is that PPARα activation may prevent these abnormalities [50,53] .…”
Section: Introductionmentioning
confidence: 99%
“…They act as intracellular sensors for free fatty acids and cholesterol metabolism and are major regulators of cell metabolism as well as cell differentiation and cellular homeostasis (185,186). PPARα promotes fatty acid mitochondrial β-oxidation, thereby decreasing steatosis (187)(188)(189). Farnesoid X receptor (FXR) acts as a sensor for bile acids and inhibits bile acid synthesis if the bile acid pool is increased, thereby protecting hepatocytes from the toxic effect of bile acids (190).…”
Section: Different Underlying Pathophysiologies and Therapeutic Implimentioning
confidence: 99%